Biosynthesis of novel non-proteinogenic amino acids β-hydroxyenduracididine and β-methylphenylalanine in Escherichia coli - Gillane, Rosemary; Daygon, Dara; Khalil, Zeinab G.; Marcellin, Esteban (Frontiers in Bioengineering and Biotechnology, 2024)
Non-proteinogenic amino acids (npAAs) are valuable building blocks for the development of advanced pharmaceuticals and agrochemicals. The surge in interest in their synthesis is primarily due to the potential to enhance and diversify existing bioactive molecules. This can be achieved by altering these bioactive molecules to improve their effectiveness, reducing resistance compared to their natural counterparts or generating molecules with novel functions. Traditional production of npAAs in native hosts requires specialized conditions and complex cultivation media. Furthermore, these compounds are often found in organisms that challenge genetic manipulation. Thus, the recombinant production of these npAAs in a model organism like Escherichia coli paves the way for groundbreaking advancements in synthetic biology. For the first time, we report the synthesis of npAAs β-methylphenylalanine (BmePhe), β-hydroxyenduracididine (BhEnd), and enduracididine (End) from Streptomyces hygroscopicus in E. coli. Through proteomic and metabolomic analyses, we achieved the production of these compounds from two synthetic operons, comprising five heterologous proteins. Interestingly, we discovered that the exogenous addition of pathway precursors to the E. coli system enhanced the yield of BmePhe by 2.5 times, whereas it concurrently attenuated the production of BhEnd and End, signifying a selective precursor-dependent yield enhancement. This study broadens the synthetic biology landscape by expanding the repertoire of amino acids beyond the conventional set of twenty-two standard proteinogenic amino acids. The biosynthesized npAAs, End, BhEnd and BmePhe hold promise for engineering proteins with modified functions, integrating into novel metabolites and/or enhance biologics' stability and activity. Additionally, these amino acids' biological production and subsequent purification present an alternative to traditional chemical synthesis methods, paving a direct pathway for pharmacological evaluation.